2014
DOI: 10.1105/tpc.114.125815
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Analysis of Arabidopsis thaliana Phospho-Proteomics Data Reveals Compartmentalization of Phosphorylation Motifs

Abstract: ORCID ID: 0000-0001-9536-0487 (K.J.v.W.)Protein (de)phosphorylation plays an important role in plants. To provide a robust foundation for subcellular phosphorylation signaling network analysis and kinase-substrate relationships, we performed a meta-analysis of 27 published and unpublished in-house mass spectrometry-based phospho-proteome data sets for Arabidopsis thaliana covering a range of processes, (non)photosynthetic tissue types, and cell cultures. This resulted in an assembly of 60,366 phospho-peptides … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

18
178
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 173 publications
(198 citation statements)
references
References 92 publications
(136 reference statements)
18
178
2
Order By: Relevance
“…Using this strategy, we identified a total of 2104 unique phosphosites, spanning 1586 phosphopeptides on 1080 proteins from unfractionated Arabidopsis seedling lysates (supplemental Table S1). These numbers are similar in size to previously reported phosphoproteome data sets (40,59). When compared with other global phosphoproteome studies we found that 159 phosphopeptides are newly reported (supplemental Table S2) (59).…”
Section: Identification Of Phosphopeptides Under Ll In Arabidop-supporting
confidence: 74%
See 1 more Smart Citation
“…Using this strategy, we identified a total of 2104 unique phosphosites, spanning 1586 phosphopeptides on 1080 proteins from unfractionated Arabidopsis seedling lysates (supplemental Table S1). These numbers are similar in size to previously reported phosphoproteome data sets (40,59). When compared with other global phosphoproteome studies we found that 159 phosphopeptides are newly reported (supplemental Table S2) (59).…”
Section: Identification Of Phosphopeptides Under Ll In Arabidop-supporting
confidence: 74%
“…These numbers are similar in size to previously reported phosphoproteome data sets (40,59). When compared with other global phosphoproteome studies we found that 159 phosphopeptides are newly reported (supplemental Table S2) (59). The distribution of phosphorylation events was Ser (89%), Thr (10%), and Tyr (1%) (supplemental Fig.…”
Section: Identification Of Phosphopeptides Under Ll In Arabidop-supporting
confidence: 72%
“…Light-dependent phosphorylation modulates the activity of proteins involved in photosynthesis (Bellafiore et al, 2005;Bonardi et al, 2005;Pesaresi et al, 2009;Rochaix et al, 2012). Analysis of 27 phosphoproteomic data sets of Arabidopsis (Arabidopsis thaliana) protein extracts identified over 60,000 phosphorylation sites in 8,141 proteins (van Wijk et al, 2014) with over 300 identified to be plastid localized (Schönberg et al, 2014). Important chloroplast processes, including metabolism, photosynthesis, gene expression, and signaling, are often controlled by protein phosphorylation in acclimation to environmental changes (Bellafiore et al, 2005;Bonardi et al, 2005;Salinas et al, 2006;Baginsky and Gruissem, 2009).…”
mentioning
confidence: 99%
“…Many of the phospho-Tyr-containing peptides were identified in analyses that applied multistage activation to elevate fragment ion intensity in spectra dominated by the neutral loss of phosphoric acid from phosphoSer and/or phospho-Thr, sometimes in combination with searches for the phospho-Tyr-specific immonium ion at mass-to-charge ratio 216.0426 (see table 1 in van Wijk et al, 2014). In one instance, phospho-Tyr-specific antibodies were used to enrich Tyr phosphorylated proteins from Arabidopsis full cell extracts (Mithoe et al, 2012).…”
mentioning
confidence: 99%
“…However, mass spectrometry-based phosphoproteomics experiments with plant cell extracts reported phospho-Tyrcontaining peptides in chloroplasts but surprisingly not in abundant thylakoid membrane proteins or Calvin cycle enzymes. A recent meta-analysis collated data from 27 published studies and several internal data sets, resulting in a cumulative data set with 5% Tyrphosphorylated peptides in the entire data set and 12% to 19% in the mitochondria (van Wijk et al, 2014). In this data set, almost 30% of the plastid phosphoproteins are flagged as Tyr phosphorylated (90 proteins from around 300; see supplemental table 5B in van Wijk et al, 2014), standing in stark contrast to dedicated plastid phosphoproteome analyses that identified less than 1% Tyr phosphorylation in the cellular phosphoproteome and none in chloroplast proteins (Reiland et al, 2009).…”
mentioning
confidence: 99%